Preservative Effects of Ginger (Zingiber officinale), Tumeric (Curcuma longa) Extract and Citric Acid and Pasteurization on the Nutritional Quality and Shelf Life of Tiger-Nut Non-Dairy Milk - Ajayi, Olasunmbo A; Bankole, Toluwalope I (Journal of Food Technology Research, 2020)
Tiger nut (Cyperus esculentus) non-dairy milk is a plant milk and a rich source of nutrients. However, milk from animal or plant is highly perishable. The focus of this study was to evaluate the influence of inclusion of preservatives and pasteurization on the quality of tiger nut milk. Five samples were produced: control (0 % preservative); natural preservatives (ginger or tumeric extract); combination of ginger and turmeric and manufactured citric acid. Samples were stored at room and refrigeration temperatures and evaluated for 30 days. Analyses performed include physico-chemical and nutritional composition, microbial load and general acceptability of tiger nut non-dairy milk samples using standard methods. Tiger nut non-dairy milk without preservative was generally accepted, while milk with ginger extract scored higher in appearance. Values ranged from (5.9 - 6.1), (5.2 - 6.8), (4.8 - 6.5); and (0.05 - 0.17 %); (0.04 – 0.15%); (0.05 – 0.17 %) for 0; 15 and 30 days respectively for pH and total titratable acidity. Total viable counts were (<1 to 5.9±1.8ax106 CFU/mL); enterobacteriaceae, (<1 to 5.4±0.7ax106 CFU/mL), Staphylococcal (3.3±1.0d x105 to 4.2±0.9bx106 CFU/mL) and fungal (<1 to 4.5±0.5ax106 CFU/mL). Moisture content (85.6 to 87.8 %), protein (3.7 - 4.3 %), ash (0.7– 1.8 %), crude fat (3.5 – 4.57 %). Sodium and potassium content ranged from (178.2 - 431.9 mg/kg) and (52.5– 416.2 mg/kg) respectively. The L* value ranged from (75.2–79.7). Conclusively, tiger nut non-dairy milk with natural preservative was as effective as manufactured citric acid in reducing the microbial content and maintaining the nutrients.